KOMUNIKASI ANTARPRIBADI MURID TUNA GANDA RUNGU WICARA DALAM PENYESUAIAN DIRI TERHADAP LINGKUNGAN SOSIAL DI USIA REMAJA (STUDI INTERAKSIONISME SIMBOLIK PADA MURID TUNA GANDA RUNGU WICARA SMALB YAYASAN PUTRA PANCASILA MALANG) - Illahi, Azizun Kurnia; Saleh, Akhmad Muwafik; Riani, Yuyun Agus (Jurnal Interaktif, 2010)
Doing self adaptation is not easy. It needs (a) long process. The self adaptation to the society cannot be separated from the interaction and communication process, within this research was called as interpersonal communication. Adaptation is not only needed by a person who has a normal sensory. But it is also needed by someone that has incomplete sensory capability, (such) as double disability mute and deaf.The theme of interpersonal communication of double sensory disability deaf and mute adaptation to the social environment was taken because the context of the double sensory disability people must do activities (like) normal people. It makes researcher want to know more about the daily living of those people who have sensory ability limitation. This research is interesting because the sources are people with double sensory disability. Besides, in this research the researcher is going to learn vocal non-verbal language and also symbolic language that has been used in their daily life.The type of research that will be used in this research is qualitative and using symbolic interaction as the approaches. For the first time, symbolic interaction was introduced by Herbert Blumer in 1962. Herbert Blumer said that words of symbolic interaction refered to the typical character from interaction that happen between human. The typicality especially in a fact that human interpret or define action between one another and not suddenly react without a reason or reciprocal. So, human interaction is mediated by the usage of symbols, by interpretation or defining meaning of others actions.     Based on the result of the research and the explanation also based on the matter point, this research could be concluded that double sensory disability people of deaf and mute, do activities as the people with no sensory disability. They can socialize with the society and have strong will to be success. The interaction and also interpersonal communication that being done help them to built their self concept. The most influential factor on their self adaptation is experience. Bad experience can cause bad personality and it could be happen at the opposite.Key words:  Symbolic interaction, interaction, interpersonal communication.